A homologue of the fungal tetraspanin Pls1 is required for Epichloë festucae expressorium formation and establishment of a mutualistic interaction with Lolium perenne. (22nd April 2019) - Green, Kimberly A.; Eaton, Carla J.; Savoian, Matthew S.; Scott, Barry
Summary: Epichloë festucae is an endophytic fungus that forms a mutualistic symbiotic association with the grass host Lolium perenne . Endophytic hyphae exit the host by an appressorium‐like structure known as an expressorium. In plant‐pathogenic fungi, the tetraspanin Pls1 and the NADPH oxidase component Nox2 are required for appressorium development. Previously we showed that the homologue of Nox2, NoxB, is required for E. festucae expressorium development and establishment of a mutualistic symbiotic interaction with the grass host. Here we used a reverse genetics approach to functionally characterize the role of the E. festucae homologue of Pls1, PlsA. The morphology and growth of Δ plsA in axenic culture was comparable to wild‐type. The tiller length of plants infected with Δ plsA was significantly reduced. Hyphae of Δ plsA had a proliferative pattern of growth within the leaves of L. perenne with increased colonization of the intercellular spaces and the vascular bundles. The Δ plsA mutant was also defective in expressorium development although the phenotype was not as severe as for Δ noxB, highlighting potentially distinct roles for PlsA and NoxB in signalling through the NoxB complex. Hyphae of Δ plsA proliferate below the cuticle surface but still occasionally form an expressorium‐like structure that enables the mutant hyphae to exit the leaf to grow on the surface. These expressoria still form a septin ring‐like structure at the point of cuticle exit as found in the wild‐type strain. These results establish that E. festucae PlsA has an important, but distinct, role to NoxB in expressorium development and plant symbiosis.